Criação de valor econômico em cooperativas agroindustriais - Santos, Ercilio (2002)
The subject of this study is the financial management and economic value addition in three cooperatives located in the southern region of Minas Gerais state. The general purpose ofthe research consisted in the identification of economic value addition from the concept of EVA (Economic Value Added). Specifically, the study searched the analysis of working capital investment and financing decisions and the financial structure of the cooperatives as a basis of value addition. Therefore, the theoretical approach of the study was the financial decisions of the firm, preceded by a literaturereview about the cooperatives, emphasizing the specificities of capital structure of these enterprises. The research was developed through case studies and the balance sheets from 1995 until 1999 as data source. The analytical model was the Fleuriet Model that provides a dynamic analysis of the enterprise's financial management through the measurement of the variables Working Investment, Working Capital and Treasury Balance. The results indicated economic value destruction, indicating that the results gained from operational activities expressed through the Operational Cash Flow were unable to remunerate the weighted average cost of capital. Regarding the working capital, the cooperatives demanded resources for the maintenance and development of operations. However, the financing of working investment was not plenty satisfíed by long run resources. There was necessity of onerous short run resources in order to finance the working investment. The combination of Fleuriet Model variables provided the identification of two basic financial structures: the solid financial situation and the dissatisfied financial situation. A general conclusion of this study refers to the diffículty ofintegration between the financial theory and cooperatives doctrine. However, with the adaptations provided by Fleuriet Model was possible to accomplish an analysis of the cooperatives financial management as a basis of economic value addition with the same tools ofanalysis used by capitalist enterprises.